Feasibility study on SMS and e-mail current awareness service for the St. Luke's Medical Library - Palac, Catherine Y.; Obille, Kathleen Lourdes B. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2009)
The expanding knowledge of medicine leads to the growing information needs of medical practitioners, researchers and medical students. Because of this, there should be a great improvement on the means by which updates like new breakthroughs, discoveries of new diseases and drugs to treat them, can be disseminated. To support the needs of the library users, medical libraries provide services that would notify them about the current information about the library which is known as Current Awareness Service (CAS). Today, some of the technologies that are commonly used by most library users are the mobile phone and electronic mail (email).
This study explored the acceptability and possibility of including SMS and E-mail as a method of providing current awareness services to the users of St. Luke's Medical Library. The objectives of this study are as follows: identify the status of the proposed SMS and E-Mail Current Awareness Service (CAS) as determined by the three elements of a feasibility study namely Market Analysis, Technical Study and Financial Study; to determine the factors that affect the possible implementation of the proposed SMS and E-Mail CAS and to present possibilities of promoting SMS and E-Mail CAS in the St. Luke's Medical Library.
This study used the descriptive research design. Survey forms were handed to 125 students and 110 were utilized in this study for market analysis. There was also a consultation with the Chief Librarian regarding the technical and financial capabilities of their library in relation to the proposed CAS.
For market analysis, findings show that all the respondents have mobile phones and e-mail accounts and were observed to be technically knowledgeable in using these technologies. For SMS dissemination, 44 of the respondents agreed for CAS delivery on a weekly basis, 36 said it should be monthly, 4 wrote for daily, 13 do not want this service and 3 did not answer this part of the survey. In addition, majority of the respondents (49) preferred to receive information updates about the newly acquired books by the library in their mobile phones. For email dissemination, 39 agreed for a monthly basis, 37 said it should be weekly while 14 wrote for daily, 6 preferred not to receive any alert messages and 4 did not answer this part of the survey.
Majority of the respondents preferred to receive information updates about the medical breakthroughs and new technologies in their email. It was also found out that the respondents disagree that alert message through SMS and e-mail is irritating, an invasion of privacy, and should not be implemented. Factors such as busy schedule of the respondents and their frequency of visits would not be affected by the proposed CAS. For technical study, the librarians and library users both agree that the library could support these components of the study. For financial study, both respondents (students and librarians) agree that the administration could allocate budget for the proposed CAS.
Based from the findings, it is therefore concluded through SMS and email is feasible at St. Luke's Medical Library. Moreover, the proposed CAS was approved by students and librarians as determined by the three elements of the feasibility study since all the respondents from the three components accepted the proposal.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: St. Luke's Medical Center Library; Current awareness services -- Philippines -- Quezon City